Experimental natural substrate preference of southern king crab Lithodes santolla larvae - Tapella, Federico (2012)
Notwithstanding the commercial importance of Lithodes santolla in the southern tip of South America, little is known about settlement habitat and behavior of their larvae. Such information is relevant for understanding its life history and for management and development of fishery-stock enhancement programs. The aims of this study were to determine the natural substrata that larval stages, zoeae and megalopa select for recruitment, and the effects of megalopa density and diurnal-nocturnal phase on such selection. Different laboratory experiments with durations of 8 hours to 4 weeks were performed in 6-L round containers with their bottoms divided in four equal portions, each filled with sand, gravel, cobble and broken shell as substrata. Containers were kept in a cold room at 7.1 ± 0.5 ºC and under 12:12 h light and dark photoperiod. Trials began with the release of larvae of different stages in the center of the containers. After different time periods, proportions of larvae swimming or settled on each substrate were determined. Larvae selected and settled on natural substrata immediately after being placed into the containers. Experiments showed that all larval stages (zoeae and megalopa) preferred complex substrata such as broken shell, cobble and gravel over sand which was rejected. The megalopa select the substrate even during night period. Selection seems to be density-dependent since at the lowest density broken shell was the preferred substrate. Selection of complex substrata (i.e. mussel beds and/or shell fragments in nature) by all larval stages, even as early as the first zoea stage, provides a cryptic habitat which may reduce mortality by predation and/or cannibalism. Knowledge on habitat preference is useful for fishery management and also for assessing the different habitats in a potential stock enhancement program of southern king crab.